Development of a knowledge-based system using C++ and unix - Ong, Eng Huat. (2009)
This thesis addresses the development of a dynamic frame-based system using C++ programming language. With this dynamic frame-based representation as a framework, an object-oriented AI environment, KBE (Knowledge Base Environment) was developed to demonstrate the usability of the dynamic frame-based system for capturing knowledge dynamically. It further demonstrates the friendliness of KBE in developing knowledge-based applications with an example of knowledge-based modelling and simulation using KBE.